The Relationship between Academic Administration and Parents’ Involvement in School Education in The Daughters of Mary Help of Christians Schools in Thailand. - Mason, Phakamas; Darbavasu , Sajeewan (Saengtham College Journal, 2021)
The research aimed 1) to study the academic administration of The Daughters of Mary Help of Christians Schools in Thailand 2) to study parents’ parti-cipation in educational management of The Daughters of Mary Help of Christians Schools in Thailand 3) to study the relationship between the roles of school administrators and parents’ participation in educational management of The Daughters of Mary Help of Christians Schools in Thailand. The sample group used in this study was 370 students’ parents learning at The Daughters of Mary Help of Christians Schools in Thailand. The instrument is the questionnaire and analyzed data analyzed by using frequency distribution statistics, percentage, mean, standard deviation and finding the correlation coefficient by The Pearson test. Research findings were as follows. 1. Pertaining to the academic administration of schools under The Daughters of Mary Help of Christians Schools in Thailand, the overall result was in the high level in all aspects, which included teaching and learning ,the development and use of technology for education, the curriculum development and research for improving educational quality in schools respectively while the last one was academic promotion and support for communities and families. 2. Regarding parents’ participation in educational management of in the affiliated schools of The Daughters of Mary Help of Christians Schools in Thailand, in general, recorded a high level in all aspects which included campaigning and supporting school activities, the promotion of learning development, the setting up of guidelines for development and operational planning of educational institutions respectively. While the last one curriculum for educational institutions . 3. The academic administration and parents’ participation in educational management at The Daughters of Mary Help of Christians Schools in Thailand revealed a high relationship posted a significant statistic level of 0.01 and correlation coefficient (r) .714, .722, .692, .734 and .726 respectively.